1989
DOI: 10.1177/019459988910000204
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CSF Rhinorrhea by Computerized Tomography with Metrizamide

Abstract: This study evaluates the ability of metrizamide computerized tomographic cisternography (MCTC) to delineate the site of leakage in patients with cerebrospinal fluid (CSF) rhinorrhea. From 1981 to 1986, thirteen patients were examined by MCTC to localize the site of CSF leakage. A total of 17 studies were performed. Thirteen scans (76%) identified the site of CSF leakage. Nine of these scans were confirmed surgically. The other four scans were performed on patients who refused surgery. Of the 15 scans in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 19 publications
0
23
0
1
Order By: Relevance
“…3 When active leaks were present, CT cisternography provided positive results in 85% of patients. 27 However, in cases of inactive fistulas, CT cisternography failed to recognize the site of leakage in 27.7% 28 and in 19% of patients. 29 Advances in CT and MR imaging techniques have improved sensitivity, which amounted to 88.25% 30 and 93% 31 for high-resolution CT and for MR cisternography to 89%, 6,31 93.6%, 28 and 100% 32,33 even in patients with inactive leaks.…”
mentioning
confidence: 99%
“…3 When active leaks were present, CT cisternography provided positive results in 85% of patients. 27 However, in cases of inactive fistulas, CT cisternography failed to recognize the site of leakage in 27.7% 28 and in 19% of patients. 29 Advances in CT and MR imaging techniques have improved sensitivity, which amounted to 88.25% 30 and 93% 31 for high-resolution CT and for MR cisternography to 89%, 6,31 93.6%, 28 and 100% 32,33 even in patients with inactive leaks.…”
mentioning
confidence: 99%
“…[16,17] MRI shows the cerebral tissue and soft tissue thoroughly, which is especially important in case of encephalocele. [18] In a study conducted on twenty-four patients, MRI has been reported to be 100% sensitive in demonstrating CSF leaks. [19] In an extensive review, all of the CSF leaks detected through MRI have been surgically verified.…”
Section: Discussionmentioning
confidence: 99%
“…CTC is accepted as the most accurate method for the investigation of active cranial CSF leakage, but it has a number of disadvantages. The sensitivity of CTC ranges between 72% and 81%, 3,25 and CTC may have problems in detecting lowflow fistulas or fistulas with only hairlike communications. This is because iodinated contrast media do not distribute freely in the CSF spaces due to their tendency to form sediment or because the tiny amount of dilute contrast medium that leaks through a fistula cannot be distinguished from the surrounding bone.…”
Section: Discussionmentioning
confidence: 99%